The struggle for northern Epirus (An Army History Directorate Publication, 2000)
This publication narrates the struggle of Hellenism after the end of the Balkan wars and in particular the 1914 Autonomy Armed Force along with the military, political and diplomatic events regarding the delicate area of Northern Epirus till 1940. The writer hopes to motivate the present and future generations, with the united national pulse of the specific period, when all Greeks were united in national pantry with all their heart to engage in a grand struggle for the liberation of their enslaved nation.